NURSES’ KNOWLEDGE AND ADHERENCE TO CLINICAL PRACTICE GUIDELINE TO PREVENT EXTRAVASATION OF CHEMOTHERAPY IN ERBIL CITY - Ismael, Dler Hamad; Qadir, Chnar Salahaddin; Mahmod, Azaddin Kamal (Journal of Sulaimani Medical College, 2025)
Background Knowledge is the cornerstone of providing safe nursing care. However, to do so, they require access to the most recent clinical information and guidance. Objectives This study aimed to determine the nurses’ knowledge and adherence to clinical practice guidelines to prevent chemotherapy-related extravasation Materials and Methods Descriptive cross-sectional design was used, 70 oncology nurses who administer chemotherapeutic drugs were selected in both Rizgary Teaching Hospital and Nanakaly Hospital for blood disease in Erbil City, from June 2022 to May 2023, data was collected through a structured interview questionnaire consisting of demographic data of nurses, knowledge about extravasation of chemotherapy, adherence to clinical practical guideline and barrier adherence to clinical practical guideline, data analyzed by using mean, standard deviation, frequency, percentage, Chi-square and binary logistic regression were used to find out the result of the study, and, a p-value less than 0.05 is considered significant. Results Concerning the overall level of knowledge of oncology nurses 55.7% had inadequate knowledge, 61.4% of them had low adherence to clinical practice guidelines, and the factors associated with low adherence to clinical practice guidelines was lower level of education (P-value=0.007, OR= 0.63), inadequate knowledge, (P-value= 0.041, OR=6.48), and high perceived barrier (P-value=0.004, OR= 9.87), the most commonly reported barriers was lack of continuing education to update nursing information and poor applicability of clinical practice guideline in real-world practice. Conclusion The clinical practice guideline adherence rate of nurses concerning chemotherapy administration was low because most oncology nurses had inadequate knowledge and high perceived barriers consequently the study highlighted the significance of continuing education to maintain oncology nursing staff with the updated evidence-based guidelines.
Keywords: Oncology nurse; Knowledge; Clinical practice guideline; Chemotherapyrelatedextravasation